The Cultivation of Professional Identity in Medical Students Based on the Interaction Ritual Chain Theory - Li JIANG (Yixue yu zhexue)
Cultivating and enhancing the professional identity of medical students is an urgent need to promote the personal development and deepen the reform of medical education. The theory of interaction ritual chains is highly suitable for analyzing the formation and evolution of medical students' professional identity. Collective gathering, boundary establishment, emotional connection, and cultural symbol sharing are key elements in the formation of medical students' professional identity. These elements, through the continuity, embedding, and extensibility of interaction ritual chain, promote the identification and internalization of the value, responsibility, and mission of the medical profession. Innovating interaction rituals, strengthening situational learning, and reshaping professional spirit can alleviate the difficulties in cultivating and enhancing the professional identity of medical students.